2021
DOI: 10.1101/2021.04.21.440756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tonic interferon restricts pathogenic IL-17-driven inflammatory disease via balancing the microbiome

Abstract: Maintenance of immune homeostasis involves a synergistic relationship between the host and the microbiome. Canonical interferon (IFN) signaling controls responses to acute microbial infection, through engagement of the STAT1 transcription factor. However, the contribution of tonic levels of IFN to immune homeostasis in absence of acute infection remains largely unexplored. We report that STAT1 KO mice spontaneously developed an inflammatory disease marked by myeloid hyperplasia and splenic accumulation of hema… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…Furthermore, STAT1-deficient mice displayed delayed WBC and platelet rebounds following 5-FU, although concomitant effects on progenitors may also contribute to this delayed rebound. These results are consistent with a recent study, which reported that HSCs in STAT1KO mice were expanded, but displayed reduced function after transplantation or 5-FU 58 . Our scRNAseq analysis showed that STAT1 loss altered several pathways that modulate HSC function including cholesterol biosynthesis 38,39 , ER stress 40 and cell cycle 6,7,41 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, STAT1-deficient mice displayed delayed WBC and platelet rebounds following 5-FU, although concomitant effects on progenitors may also contribute to this delayed rebound. These results are consistent with a recent study, which reported that HSCs in STAT1KO mice were expanded, but displayed reduced function after transplantation or 5-FU 58 . Our scRNAseq analysis showed that STAT1 loss altered several pathways that modulate HSC function including cholesterol biosynthesis 38,39 , ER stress 40 and cell cycle 6,7,41 .…”
Section: Discussionsupporting
confidence: 93%
“…The potential of type I IFN or IFN-stimulated gene (ISG) products to accelerate cDC activation and enhance immune reactivity in neonates suggests a functional role. Whereas enhanced IFN and ISG expression during viral infection has long been described (Mesev et al, 2019), a number of reports also described tonic expression in healthy animals with comparable levels in primary and secondary immune organs and small intestine (Abt et al, 2012; Ganal et al, 2012; Lienenklaus et al, 2009; Marie et al, 2021; Schaupp et al, 2020). Plasmacytoid (p)DCs represent the most likely source of this tonic type I IFN (Schaupp et al, 2020) but cDCs also directly sense IFN-inducing microbial stimuli (Cabeza-Cabrerizo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Such interaction between the microbiome and the immune system helps regulate the balance between protective immunity and tolerance to harmless microorganisms and environmental stimuli. Tonic IFN-I signaling also contributes to the overall surveillance of the immune system, priming it to respond rapidly and effectively to potential threats such as viral infections (Gough et al, 2012;Bradley et al, 2019;Marie et al, 2021). Moreover, it aids in the maintenance of tissue integrity and barrier function, further bolstering the body's defenses against pathogens.…”
Section: Tonic Brain Ifn-i Signalingmentioning
confidence: 99%